The consecration of languages through translation awards in Sweden (1970–2015) - Dahl, Alva; Svahn, Elin (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2021)
This paper examines the role of translation awards in strengthening the literary capital of source languages. Focusing on three Swedish translation awards between 1970 and 2015, and comparing the awarded source languages to 1) the most central and influential literary languages in world literature and 2) Swedish publishing statistics 1970–2015, the aim is to position translation awards as an area of research within Translation Studies, as well as to investigate translation awards as a means of consecrating source languages in the target culture. Furthermore, we ask how these translation awards transfer different forms of symbolic capital back to the awarding institutions. The results from the comparisons show both similarities and differences, indicating that in the Swedish literary field, there are slight variations to the general global hierarchy of languages. The awarding patterns from the three translation awards studied are also in line with the profiles of the different awarding institutions. As could be expected, English is the most awarded language, although its dominance is strikingly small when compared to publishing statistics. This indicates that the literary capital of English is not unlimited; semi-central or even peripheral languages can transfer other sorts of values to the awarding institutions.